THE EFFECT OF ACCOUNTING CONSERVATISM ON THE ECONOMIC DECISIONS OF INVESTORS / A STUDY IN A SAMPLE OF IRAQI BANKS LISTED ON THE IRAQI STOCK EXCHANGE - Maha Sahl Kazem; Assist. Prof. Dr. Karrar (Scholar Express Journals, 2022)
The aim of the current research is to analyze the intellectual and applied impact of the accounting reservation on the economic decisions of investors, by applying to 130 views (company / year) in Iraqi banks listed in the Iraq Stock Exchange for the period from 2011-2020 . The variables of this study were measured quantitatively, the accounting conservatism was measured using the receivables model, and the economic decisions of investors were measured through the volume of trading in shares. Among the most important findings of the research: that there is a direct effect between accounting conservatism and investors’ decisions, and this indicates the tendency of investors towards accounting conservatism as it contributes to preserving the company’s assets. The company in investor decisions .
Keywords: accounting conservatism; economic decisions; investors